The Forms of Historical Fiction Sir Walter Scott and His Successors - Shaw, Harry E. (Cornell University Press, 2018)
Harry Shaw's aim is to promote a fuller understanding of nineteenth-century historical fiction by revealing its formal possibilities and limitations. His wide-ranging book establishes a typology of the ways in which history was used in prose fiction during the nineteenth century, examining major works by Sir Walter Scott-the first modern historical novelist-and by Balzac, Hugo, Anatole France, Eliot, Thackeray, Dickens, and Tolstoy.